Corticosteroides para o tratamento de crianças e adultos com sepse: uma Revisão Cochrane - Annane, Djillali; Bellissant, Eric; Edouard Bollaert, Pierre; Briegel, Josef; Keh, Didier; Kupfer, Yizhak; Pirracchio, Romain; Rochwerg, Bram (LAJEC - Latin American Journal of Emergency Care, 2022)
h